Pengaruh Struktur Modal, Ukuran Perusahaan, dan Pertumbuhan Penjualan terhadap Nilai Perusahaan dengan Intervening Kinerja Keuangan - Akwilia, Asteria; Espa, Vitriyan; Desyana, Gita (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Company value is the main factor that describes market conditions on the performance and possibilities of a company. The purpose of this study is to analyze the effect of capital structure, company size, and sales growth on company value, with financial performance intervening. Research with associative quantitative analysis using secondary data, namely the annual financial reports of companies in the Fast-Moving Consumer Goods sector published on the Indonesia Stock Exchange (IDX) from 2022–2024. The sample was selected through a purposive sampling method, in 30 companies that met the criteria and a sample of 90. Using path analysis techniques to find out the direct and indirect relationships of each variable. The results of this study prove that partially, capital structure and company size do not affect company value or financial performance. Sales growth does not have a direct effect on company value, but affects financial performance, which then has a significant impact on company value. Simultaneously, capital structure, company size, and sales growth do not affect financial performance, but significantly affect company value through financial performance as an intervening variable.